Group Horticulture Program on Psychiatric Symptoms in Patients with Chronic Schizophrenia - Neda Parvin; Leila Rafiee Vardanjani; Fatemeh Aliakbari (Golestan University of Medical Sciences, 2017)
Background: Schizophrenia is a devastating psychiatric disorder and its  Positive and negative symptoms have negative effects on social functions. A combination of pharmacological and non-pharmacological treatments is considered more effective for this condition. The present study aimed to determine the effect of a group horticulture program on psychiatric symptoms in patients with chronic schizophrenia. Methods: This quasi- experimental study was conducted from April 2014 to July 2014 in Sina Hospital in Chahar Mahal and Bakhtiari province in Iran. Fifty-two eligible patients with diagnosis of chronic schizophrenia were randomly assigned to two groups of horticulture and usual care (control). Both groups received similar medical and routine care. The patients in horticulture group participated in a group horticulture program for three months. The patients’ psychiatric symptoms were evaluated at the beginning and at the end of the study by Andreasen’s scales for assessment of negative and positive symptoms. The data was analyzed by student t test, paired t test and chi square.  Results: At the beginning of the study, the patients in both study groups were matched in terms of age, sex, marriage status, education, and average scores of positive and negative symptoms. At the end of the study, the horticulture group showed a significant improvement compared with control group in positive and negative symptoms (P < 0.05), which indicated the effectiveness of the intervention on these symptoms. Conclusion: Group horticulture program can be used as an effective non-pharmacological adjunctive treatment in patients with chronic schizophrenia.